The Strength and Conditioning Journal (Strength and Conditioning Journal)
Homepage of the Strength and Conditioning Journal which is the professional journal for strength coaches, personal trainers, athletic trainers, physical therapists, and other health professionals working in the strength and conditioning field. The journal's mission is to publish articles that report both the practical applications of research findings and the knowledge gained by experienced professionals. This mission includes, whenever possible, integrating both sources of knowledge, providing practitioners with the most accurate information available.